The effect of Chinese culture-adapted dignity therapy on advanced cancer patients receiving chemotherapy in the day oncology unit: A quasi-experimental study. (April 2023) - Lin, Junyi; Guo, Qiaohong; Xi, Lanxin; Zhang, Hong; Liu, Fang; Zheng, Ruishuang; Liu, Wei
Abstract: Purpose: To examine the effects of Chinese culture-adapted dignity therapy on dignity-related and psychological, spiritual distress and family function for advanced cancer patients receiving chemotherapy in the day oncology unit. Method: This is a quasi-experimental study. Patients were recruited from a day oncology unit at a tertiary cancer hospital in Northern China. A total of 39 patients agreeing to participate were assigned to receive Chinese culture-adapted dignity therapy (intervention group, n = 21) or supportive interview (control group, n = 18) according to their admission time. Patients' dignity-related, psychological, spiritual distress, and family function were assessed at baseline (T0) and after completing the intervention (T1) and the scores were compared between and within the groups. Besides, the interviews were conducted with patients at T1 to obtain their feedback, which were analyzed and integrated with the quantitative results. Results: There was no statistical significance in all outcomes at T1 between the two groups, as well as in most outcomes between T0 and T1 in the intervention groups except for the relieved dignity-related distress ( P  = 0.017), especially the physical distress ( P  = 0.026), and the improved family function ( P  = 0.005), especially the family adaptability ( P  = 0.006). The synthesized quantitative and qualitative results showed that the intervention could relieve physical and psychological distress, enhance the sense of dignity, and improve the spiritual well-being and family function of patients. Conclusions: The Chinese culture-adapted dignity therapy showed positive effects on the life experiences of patients receiving chemotherapy in the day oncology unit and their family, and it might be a suitable, indirect communication prompt for Chinese families. Highlights: Early receiving psychological support is recommended for advanced cancer patients receiving chemotherapy in outpatient settings. The quantitative and qualitative methods were used for effect evaluation of Chinese culture-adapted dignity therapy. C-DT could promisingly relieve sufferings of patients receiving chemotherapy in a day oncology unit. C-DT could promisingly improve family functions in the family-cultural context in China. C-DT could be viewed as an indirect communication prompt in Chinese families.